Relationship between Mother's Work and Success in Providing Exclusive Breastfeeding in the Work Area of Upt Puskesmas Beras Basah, Pangkalan Susu District in 2021 - Fithriani (Science Midwifery, 2022)
Getting breast milk is a human right for every baby, because breast milk is the best food for babies. Breastfeeding is the right of every mother, including working mothers. However, working mothers are still considered as one of the factors causing the high rate of breastfeeding failure. The purpose of this study was to determine the relationship between mother's work and mother's success in giving exclusive breastfeeding. The purpose of this study was to determine the relationship between maternal occupation and the success of exclusive breastfeeding in the Work Area of ​​the UPT Puskesmas Beras Basah, Pangkalan Susu District in 2021. This study used an analytical survey research design with a cross sectional approach, namely measuring independent variables and dependent variables simultaneously. The samples taken in this study were mothers who had babies aged 6-11 months as many as 72 people using a simple random sampling technique. Collecting data using a questionnaire using univariate and bivariate data analysis. The data were analyzed using the Chi-Square (x2) test. The results showed that 38 working mothers did not succeed in giving exclusive breastfeeding (80.9%) and 9 people (11.0%) succeeded. mothers who did not work succeeded in giving exclusive breastfeeding to 14 people (56.0%) and those who were not successful were 11 people (44.0%). Based on the results of statistical tests, it was found that there was a relationship between working mothers and exclusive breastfeeding in the work area of ​​the Rice Basah Health Center UPT with p-value = 0.001 (p-value <0.05) because 0.01 <0.05 then H0 was rejected and Ha was accepted, It is recommended for health workers to provide more knowledge and motivation to the community about the importance of exclusive breastfeeding. .